Soil-structure interaction analysis of well foundation - Ishwor Chandra Marahatta; Sanjay Kumar Jha; Bikash devkota (Journal of Innovations in Engineering Education, 2024)
Well (caisson) foundation has been used in bridges for a long time to withstand the heavy lateral forces and moments. A better understanding of soil-caisson interaction can help to build a safe and economic well foundation. The behavior of caisson under various soil-structure interaction scenarios was investigated in this study. Different aspects of the well foundation like load-displacement relationship and variations in axial load capacity with varying parameters of soil and caisson were studied through numerical analyses. The results showed that the load-carrying capacity of the caisson increased with the improvement of soil properties such as Young’s modulus of elasticity (Es), cohesion (C), friction angle (ϕ), and Poission’s ratio (ν) whereas cohesion and friction angle greatly influenced the well capacity. Likewise, load carrying capacity increased with an increase in grip length and diameter of the well. However, caisson’s capacity increased in higher magnitude while increasing its diameter for a constant grip length than increasing grip length for a fixed diameter.